Exploring the Credibility and Trustworthiness of Web 2.0 Tools during Covid-19 from the Eyes of Information Providers - Farhana Saeed Hashmi, Oumair Naeem, Ghulam Farid, Akhtar Ali, Muhammad Kamran, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: In addition to posing serious obstacles to international health systems, the coronavirus (COVID-19) has created a deluge of false information. During COVID-19, the librarian must have the most recent information available in their capacity as an information manager. The use and methods used by librarians to assess the validity of information and the legitimacy of Web 2.0 technology providers are examined in this study. Aim: Using a survey approach, the reliability and trustworthiness of web tools were investigated in this quantitative study during COVID-19. Method: The study's 82% response rate was sustained. In terms of representation, men remained in the majority over women. Study population: Pakistani university librarians in the public sector. It's clear that the bulk of responders 59.48% attend universities in Punjab, followed by those in Islamabad (17.24%), KPK (13.79%), Sindh (6.9%), Balochistan 1.72%), and GilgitBaltistan 0.86%. Results: The results demonstrate that web 2.0 tools had a significant impact on librarians' knowledge of health information seeking behaviors during COVID-19; however, the information they accessed on social media during the pandemic was shared information about the disease and came from discussion groups. Among other things, during COVID, web 2.0 tools' credibility and trustworthiness greatly improved, and the importance of message credibility also increased. Conclusion: The study found that web 2.0 tools for health information during Covid-19 were mainly trusted by information professionals, with discussion groups on social media being the main source of health information. The majority of respondents (59.48%) were aged 26-35, with a high trustworthiness ratio in Balochistan, Sindh, and Punjab. The study also found a high ratio in Sindh. Key words: Trustworthiness, Credibility, Web 2.0 tools, Information Providers, health information